An immobilized and highly stabilized self‐sufficient monooxygenase as biocatalyst for oxidative biotransformations. Issue 4 (15th November 2017) - Valencia, Daniela; Guillén, Marina; Fürst, Maximilian JLJ; López‐Santín, Josep; Álvaro, Gregorio
Abstract: BACKGROUND: The requirement for expensive cofactors that must be efficiently recycled is one of the major factors hindering the wide implementation of industrial biocatalytic oxidation processes. In this research, a sustainable approach based on immobilized self‐sufficient Baeyer–Villiger monooxygenases is discussed. RESULTS: A bifunctional biocatalyst composed of an NADPH‐dependent cyclohexanone monooxygenase (CHMO) fused to an NADP + ‐accepting phosphite dehydrogenase (PTDH) catalyzes ϵ‐caprolactone synthesis from cyclohexanone, using phosphite as a cheap sacrificial substrate for cofactor regeneration. Several immobilized derivatives of the fused enzyme have been prepared with high immobilization yield (97%); the one obtained by affinity adsorption on Co‐IDA (Co: cobalt chelated; IDA: iminodiacetic acid) support has shown to be highly stable affording average yields of 80% after 18 reaction cycles. CONCLUSIONS: The immobilized self‐sufficient monooxygenase has demonstrated to be able to perform Baeyer–Villiger oxidation with efficient cofactor recovery and biocatalyst recycling. The proposed biocatalytic process offers access to valuable molecules with high atom economy and limited waste generation. © 2017 Society of Chemical Industry